Analisis Kebutuhan Video Pembelajaran dan Implementasi PMRI untuk Mengetahui Kemampuan Pemecahan Masalah Siswa - Muhammad Nur Aula; Zulkardi Zulkardi; Cecil Hiltimartin (Media Pendidikan Matematika, 2025)
A persistent issue in mathematics education at the elementary level is students’ difficulty in comprehending problems, which consequently leads to low learning outcomes. This study aims to analyze teachers’ and students’ needs as well as their experiences in mathematical problem solving. A descriptive qualitative method was employed, involving 30 student respondents and 12 teacher respondents. Data were collected through a needs analysis questionnaire concerning the learning media currently used. The results indicate that, in general, the preferred learning media include images and videos that can be accessed repeatedly at any time, provide explanations accompanied by examples, have a duration of 5–10 minutes, and incorporate real-life problem contexts. Moreover, the most effective learning process is suggested to employ real-world contexts through the PMRI (Indonesian Realistic Mathematics Education) approach. Students’ problem-solving experiences serve as indicators of mathematical competence; however, the stage requiring the most instructional intervention is the implementation phase, particularly in connecting mathematical concepts to everyday life situations. The findings underscore the importance of providing learning media that align with students’ and teachers’ needs and implementing contextual approaches to enhance students’ mathematical competence.